2,3-Dihydrobenzofuran neolignans from Aristolochia pubescens - Nascimento, I. R.; Lopes, LMX (Elsevier B.V., 1999)
From a hexane extract of stems and roots of Aristolochia pubescens, the new neolignans (2S,3S,1'R,2'R)- and (2S,3S, 1'S,2'R)-2,3-dihydro-5-(1',2'-dihydroxypropyl)-2-(4-hydroxy-3-methylbenzofuran) and (2S,3S,1'R,2'R)- and (2S,3S,1'S,2'R)-2,3-dihydro-5-(1',2'-dihydroxypropyl)-2-(3,4-dimethoxyphenyl)-7-methoxy-3-methyl-benzofuran were isolated, together with the known neolignan licarin A, and its bisnor-neolignan aldehyde and acid derivatives. In addition, sitosterol, 8R,9R-oxide-beta-caryophyllene, kobusone, ent-kauran-16 alpha, 17-diol, vanillin, vanillic acid, (+)-sesamin, (+)eudesmin, and (-)-cubebin were isolated. The structures of the new compounds have been elucidated by spectroscopic methods and by chemical transformation using Mosher's acid chloride. (C) 1999 Elsevier B.V. Ltd. All rights reserved.
Keywords: Aristolochia pubescens; Aristolochiaceae; neolignans; bisnor-neolignans lignans; sesquiterpenes; diterpenes; vanillin; vanillic acid